Family social climate and its relationship with Attention Deficit Disorder in students (LACCEI, 2024)
The main objective of the present study was to determine whether the social family climate is related to attention deficit in students. The research was of an applied type, with a quantitative approach, of causal correlation scope and transectional cut, having a non-experimental-cross-sectional design. The population consisted of 692 students, using a probabilistic sample by convenience, 100 students were considered. The information in this study was obtained through the data sheet of the family social climate instrument (FES) and the data sheet of the CARAS-R instrument, reaching the conclusion that the family social climate has a significant relationship with the students' attention deficit. The results obtained in this research were 48. 5% of the attention deficit is explained by the family social climate, on the other hand, 17% mentioned that they have a bad family social climate, 54% mentioned that their family social climate is at an average level, while 13% indicated that it tends to good, 12% mentioned that their family social climate is good, finally 2% have an excellent family social climate, on the other hand, regarding the attention deficit variable, 40% of the students have attention deficit, while 36% present an average attention capacity and only 8% tend to good.